Health awareness of inhabitants of Lublin versus justifiability of calling emergency ambulance services - Wolański, Łukasz; Muzyczka, Katarzyna (Polish Journal of Public Health, 2009)
Introduction. In the present study an analysis of cases of calling emergency ambulance services in the city of Lublin in the period of twenty years in relation to the city’s development and its results was carried out. This was aimed at evaluating of changes occurring in the awareness of inhabitants with regard to self-assessment of one’s general health condition and the state of their system in the case of a disease on the basis of the symptoms experienced, as well as the compatibility of these assessments with the subsequent medical diagnosis based on the result of the medical examination. Objective. The objective of the study was to carry out an analysis of cases of calling emergency ambulance services in the city of Lublin in the period of twenty years in relation to the city’s development and results of this development. Material and method. The empirical material was collected by analysing ambulance departure cards of the Voivodeship Emergency Service of the Independent State Healthcare Centre in Lublin. There were analysed 3885 departures of emergency ambulance. For the statistical analysis of the obtained results the Chi-square test was applied, whose purpose is to assess the homogeneity and independence of non-measurable features. Results. The increase of the frequency of cases of calling emergency teams for persons aged above 70 was observed, while the number of calls for persons in age groups below 50 decreased, and in the case of people aged from 50 to 70 this number remained at a similar level. Among the results relating to the justifiability of calling an emergency team it can be mentioned that the number of women aged above 70 for whom emergency ambulance services were called when the diagnosis differed from the patient’s declaration, dropped. As far as men are concerned, a reverse tendency was noticed in the age group below 30. Conclusions. Together with urban development of Lublin, the number of cases of calling emergency ambulance services increased, which was caused by the territorial extensiveness of the city. Due to the rise of an average lifespan and of social awareness, the number of calls for the oldest part of population grew as well.